Improvement of shear capacity of RAC beams by adopting identical mortar volume method of mix-design along with dual-stage mixing approach. Issue 3 (17th February 2023) - Mandal, Romio; Panda, Sarat Kumar; Kisku, Nishikant; Rajhans, Puja; Banerjee, Susanta; Nayak, Sanket
Abstract: The shear performance of concrete beams produced from construction and demolition (C&D) waste is evaluated by considering two different shear-span to depth ratios (a/d). A total of twelve beams are cast, in which four beams of natural aggregate concrete (NAC) of conventional mix-design procedure (denoted as NAC), four beams of recycled aggregate concrete (RAC) of identical mortar volume (IMV) mix-design procedure in conjunction with normal mixing procedure (NMP) (denoted as RAC/NMP), and rest four beams of RAC of IMV mix-design procedure in conjunction with proposed dual-stage mixing procedure (DSMPSiC ) (symbolized as RAC/DSMPSiC ). Out of four beams of each of the above categories, two beams are tested by considering a/d = 2.5 and the other two are tested by considering a/d = 3. The load-deflection curve, ultimate load carrying capacity, and crack propagation parameters are also evaluated. The results are compared with different empirical relations proposed in codes and published literature. Analysing critically, it is observed that the shear strengths of RAC/NMP beams are reduced by 19% for a/d = 2.5 and 13.5% for a/d = 3 as compared to corresponding NAC beams. However, after following the proposed DSMPSiC, the above reduction percentages are reduced by 11.2% and 5.2%, respectively.